EKSPERIMEN/PENCAMPURAN TANAH LIAT STONEWARE DI UD. TRI SURYA KERAMIK MENGGUNAKAN PASIR MALANG DAN PASIR KARANGASEM PADA PRODUK TABLEWARE DAN HOME DÉCOR - Wiswambhara, Dewa Gede; Sunarini, Ni Made Rai; Mahadi, Mercu (Hastagina : Jurnal Kriya Seni, 2024)
The creation of this ceramic work aims to create a mixture of innovative materials that can be applied to stoneware soil in creating innovative ceramic products. This creation is also one of the exploration spaces in the development of creativity in conducting experiments on ceramic raw materials. The experiment was carried out by combining a mixture of Malang sand and Karangasem sand with stoneware soil in the process of realizing a ceramic body. The experimental process was carried out at the UD company. Tri Surya Ceramics which is one of the companies that takes part in making ceramics with modern contemporary nuances but still traditional nuances. Based on that, UD. Tri Surya Keramik is considered the most appropriate to bridge the space of exploration and experimentation in realizing the idea of mixing Malang and Karangasem sand with stoneware soil. Besides that, it can provide a new color for the company in the choice of materials that will later be applied in the manufacture of ceramic products. Home décor products consist of urns, straight and threaded flower fittings, while tableware products consist of plates, bowls, and glasses. The two products are glazed only on the inside, while the outside is still left natural to display the texture of the material and color caused by the mixing of stoneware soil with Malang and Karangasem sand.